The relationship between psychopathology and cognitive functions with cytokines in clinically stable patients with schizophrenia - HAKLAR, GONCAGÜL; YILDIZ, MESUT; YANARTAŞ, ÖMER; ERGÜN, SERHAT (TAYLOR & FRANCIS LTD, 2018)
OBJECTIVES: Inflammation and the cytokine hypotheses have been proposed for schizophrenia. Several proinflammatory and anti-inflammatory cytokines have been studied in drug-naive, first-episode, and/or chronic schizophrenia patients. However, there were limited data on clinical stable outpatients reflecting daily routine. The aim of this study was to compare the serum levels of cytokines, including transforming growth factor-beta (TGF-beta), interleukin-6 (IL-6), and tumour necrosis factor-alpha (TNF-alpha), between clinically stable patients with schizophrenia and healthy controls, as well as to examine the relationship between these inflammation parameters and clinical variables (positive and negative symptom severity and cognitive functions). METHODS: Thirty clinically stable outpatients with schizophrenia and 30 healthy controls with similar sex and age were included in this study. Serum IL-6, TGF-beta, and TNF-alpha levels were assessed by enzyme-linked immunosorbent assay (ELISA) and immunoenzyme microplate measurement, respectively. Illness severity was evaluated using the Positive and Negative Syndrome Scale (PANSS), and the cognitive functions of the participants were assessed using a broad neuropsychological test battery. RESULTS: The serum levels of IL-6 and TGF-beta were significantly higher in patients with schizophrenia compared to healthy controls (p = .048, p = .012). There was no significant difference between groups in terms of TNF-alpha levels (p = .726). Global impairment of cognitive functions was observed in the patient group compared to healthy controls, and PANSS scores and cognitive functions showed no correlation with cytokine levels (IL-6, TNF-alpha, and TGF-beta). CONCLUSIONS: The present study demonstrated an increased inflammatory response in clinically stable patients with schizophrenia compared to healthy controls. However, symptom severity and cognitive functions showed no correlation with cytokine levels. Further research studies are needed to clarify the effects of cytokine levels on schizophrenia symptomatology and etiopathogenesis.
Keywords: Schizophrenia; inflammation; cytokines; cognition; psychopathology; 1ST EPISODE PSYCHOSIS; SYNDROME SCALE PANSS; C-REACTIVE PROTEIN; MEDICATION-NAIVE; SERUM-LEVELS; METAANALYSIS; SYMPTOMS; INFLAMMATION; IMPAIRMENT; INDIVIDUALS